And the Dark Sacred Night - Glass, Julia 1956- (Pantheon, 2014)
"Kit Noonan's life is stalled: unemployed, twins to support, a mortgage to pay...and a frustrated wife, who is certain that, more than anything else, Kit needs to solve the mystery of his father's identity. He begins with a visit to his former stepfather, Jasper, a take-no-prisoners Vermont outdoorsman. But it is another person who has kept the secret: Lucinda Burns, wife of a revered senior statesman and mother of Malachy (the journalist who died of AIDS in Glass's first novel, Three Junes). She and her husband are the only ones who know the full story: of an accident whose repercussions spread even further when Jasper introduces Lucinda to Kit. Immersing readers in a panorama that stretches from Vermont to the tip of Cape Cod, Glass weaves together the lives of Kit, Jasper, Lucinda and, ultimately, Fenno McLeod, the beloved protagonist of Three Junes (now in his sixties). An unforgettable novel about the youthful choices that steer our destinies, the necessity of forgiveness, and the surprisingly mutable meaning of family"..